Sustainable High-rises - Babak Raji (A+BE: Architecture and the Built Environment)
With the aim to limit the number of ineffective designs, this dissertation has investigated the impact of architectural design strategies on improving the energy performance of and thermal comfort in high-rise office buildings in temperate, sub-tropical and tropical climates. As the starting-point of this research, a comparative study between twelve high-rise office buildings in three climate groups was conducted. For each climate group, three sustainable high-rises were selected and one typical high-rise design as a reference. The effectiveness of architectural design strategies was compared between the two categories of buildings (high-performance versus low-performance) concerning their potential impact on heating, cooling, lighting and ventilation loads. Certain architectural design strategies were found to be major determinants of energy performance in high-rise buildings. These can be classified under the categories of geometric factors, envelope strategies, natural ventilation strategies, and greenery systems. To quantify the extent to which these architectural design strategies affect energy use and thermal comfort of tall office buildings, simulation studies were carried out.